2020
DOI: 10.47153/jbmr15.592020
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Flexible Working Hours, Remote Working, and Work Life Balance to Employee Satisfaction in Banking Industry during Covid-19 Pandemic Period

Abstract: During the situation like Coronavirus COVID -19 pandemic that happened in 2020, forcing various banking companies to make adjustments and changes to their work system. The flexible working system is one of the most widely used, which has an impact on workers especially during this pandemic conditions. The impact of the change in work system in banking sector is interesting to study, especially since the banking industry in Indonesia still mostly uses conventional work systems. . This study aims to measure the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 8 publications
(11 reference statements)
2
4
0
1
Order By: Relevance
“…Thus, it can be stated that H0 is rejected, meaning that work-life balance and flexible work arrangement have a positive and significant effect on job satisfaction in State Senior High School Teachers in Pematang Siantar City. This is in line with the research conducted by [15] Hypothesis Source: results of questionnaire processing using SPSS (2022) The residual equation between the job satisfaction variable and the residual absolute value of the moderating variable (work stress) results in the following residual test model equation: e = 2,996 + 0,005Y The results of the residual test analysis in table 7 can be seen that the job satisfaction variable is significant > 0.05 and the value of the parameter coefficient is positive, so it can be explained that the work stress variable weakens the effect of work-life balance and flexible work arrangement on job satisfaction. Therefore, H2 which states that work stress moderates the effect of work-life balance and flexible work arrangement on job satisfaction is rejected.…”
Section: Source: Results Of Questionnaire Processing Using Spss (2022)supporting
confidence: 93%
“…Thus, it can be stated that H0 is rejected, meaning that work-life balance and flexible work arrangement have a positive and significant effect on job satisfaction in State Senior High School Teachers in Pematang Siantar City. This is in line with the research conducted by [15] Hypothesis Source: results of questionnaire processing using SPSS (2022) The residual equation between the job satisfaction variable and the residual absolute value of the moderating variable (work stress) results in the following residual test model equation: e = 2,996 + 0,005Y The results of the residual test analysis in table 7 can be seen that the job satisfaction variable is significant > 0.05 and the value of the parameter coefficient is positive, so it can be explained that the work stress variable weakens the effect of work-life balance and flexible work arrangement on job satisfaction. Therefore, H2 which states that work stress moderates the effect of work-life balance and flexible work arrangement on job satisfaction is rejected.…”
Section: Source: Results Of Questionnaire Processing Using Spss (2022)supporting
confidence: 93%
“…We also highlighted that employees are fond of technological tools, have knowledge of manufacturing technologies, and are eager to improve their well-being and satisfaction with their co-workers. This is in line with the findings of prior studies, such as that of Putra, Pratama, Linggautama, and Prasetyaningtyas [147], who found a significant relationship between the WLB and JP of bank employees and confirmed that individuals with high levels of JP would have a high level of WLB [18]. This implies that employees can perform negotiations and accomplish their work on time, and spend quality time with their family, even during the pandemic period, when resorting to WFH for more than three days due to lockdown measures [13].…”
Section: Discussionsupporting
confidence: 93%
“…Although several studies explored the consequences of WLB during the pandemic (e.g. Bhumika, 2020; Gigauri, 2020; Putra et al. , 2020; Ruzojcic et al.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Work-life balance (WLB) has been a relevant and salient topic for companies and employees during the COVID-19 pandemic (Bhumika, 2020; Möhring et al. , 2021; Putra et al. , 2020).…”
Section: Introductionmentioning
confidence: 99%